The Pengolahan Buah Mangrove Jenis Sonneratia alba Menjadi Permen Jelly di Desa Jerowaru, Kabupaten Lombok Timur - Chandrika Eka Larasati; Ayu Adhita Damayanti; Paryono; Baiq Hilda Astriana; Mahardika Rizqi Himawan; Wiwid Andriyani Lestariningsih (Universitas Mataram, 2022)
Mangrove fruit processing in Jerowaru Village is still not utilized properly. Whereas mangrove fruit has great potential to be processed into various products. One form of processed mangrove fruit is to make jelly candy. Its sweet and sour taste makes this product an alternative that is much in demand by children and adults because it contains nutrients such as carbohydrates, vitamin C, phenols to anti-oxidants for the body and can have economic value for the surrounding community. One alternative is to conduct training in the manufacture of jelly candy made from raw materials of mangrove fruit. This is done as an effort to increase added value in making local food that has nutritional and economic value. The approach method applied in this service activity is an active participation method, namely by involving coastal community groups in making jelly candy. The enthusiasm of the local community to be able to take part in this activity was high, so we limited the number of participants to 25 people. The participants of the activity included the PKK women's group, youth youth groups and the Bale Mangrove Pokmaswas group. The material presented was about the process of processing mangrove fruit into jelly candy that can be used. The results of this service activity are increasing the knowledge and skills of the participants in processing Sonneratia alba mangrove fruit into jelly candy that can be consumed by all types of people. Furthermore, jelly candy can be packaged as attractively as possible to increase marketability and can be used as a characteristic of Jerowaru Village.